2012
DOI: 10.1039/c2cp22768a
|View full text |Cite
|
Sign up to set email alerts
|

Superstructure based on β-CD self-assembly induced by a small guest molecule

Abstract: The size, shape and surface chemistry of nanoparticles play an important role in cellular interaction. Thus, the main objective of the present study was the determination of the β-cyclodextrin (β-CD) self-assembly thermodynamic parameters and its structure, aiming to use these assemblies as a possible controlled drug release system. Light scattering measurements led us to obtain the β-CD’s critical aggregation concentration (cac) values, and consequently the thermodynamic parameters of the β-CD spontaneous sel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
20
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(25 citation statements)
references
References 53 publications
(107 reference statements)
1
20
0
Order By: Relevance
“…ITC results could also provide information about the molecular stoichiometries of both systems, in which more than one guest molecule interacts with a single βCD [43]. Similar superstructures have been observed for CD systems, and in these cases, the guest molecule acted as a glue between the inclusion complexes [36]. Other studies have described interactions between CD-based polymers and guest molecules and their use as a promising drug carriers using ITC [44,45] These results strongly suggest that polyCD can be used as a polymer for DDS for hydrophilic molecules such as PROP.…”
Section: Supramolecular Guest Interaction With CD and Polycdmentioning
confidence: 71%
See 1 more Smart Citation
“…ITC results could also provide information about the molecular stoichiometries of both systems, in which more than one guest molecule interacts with a single βCD [43]. Similar superstructures have been observed for CD systems, and in these cases, the guest molecule acted as a glue between the inclusion complexes [36]. Other studies have described interactions between CD-based polymers and guest molecules and their use as a promising drug carriers using ITC [44,45] These results strongly suggest that polyCD can be used as a polymer for DDS for hydrophilic molecules such as PROP.…”
Section: Supramolecular Guest Interaction With CD and Polycdmentioning
confidence: 71%
“…[36] and this result can be attributed to a greater possibility of forming hydrogen bonds between the polymer and water. Similar systems formed by polyrotaxanes, which consisted of α-cyclodextrin and poly(ethylene glycol) (PEG), showed values with the same order of magnitude in different types of solvent systems [37].…”
Section: Characterization Of Cd-based Polymermentioning
confidence: 91%
“…As reported in literature, cyclodextrins have the ability of spontaneously self-assembly in supramolecular structures of nanometric size [15,16,42]. Moreover, it has been demonstrated that cyclodextrins form coordination complex with transition metals at high pH values (>12), in such a way that a covalent bond is formed between metal ions (Fe, Ni or Zn) and deprotonated ReOH group, i.e.…”
Section: Rheological Characterization Of Feeni/zn and Feni/zn/bcd Susmentioning
confidence: 93%
“…[46] The cavity size of β-CD is more suitable than other CDs to encapsulate a wide range of molecules. [47,48] The use of β-CD on drug solubility, bioavailability, safety, stability, and as a carrier in drug formulation may be attained by the formation of inclusion complexes with drug molecules; in fact, the use of β-CD already has a long history in pharmacy. [49,50] β-CD consists of seven glucopyranose residues and is only moderately soluble in water because of intermolecular hydrogen bonding.…”
Section: β-Cyclodextrin (β-Cd)mentioning
confidence: 99%